Distribution and source of 1-O-monoalkyl glycerol ethers in the Yellow River and Bohai Sea. (January 2016) - Wang, Yinghui; Xu, Yunping
Highlights: Up to 21 MAGE compounds were identified in soils, river and marine sediments. Their ubiquitous presence suggests MAGEs not specific for sulfate reducing bacteria. Terrestrial inputs of MAGEs are minor compared to in situ production in Bohai Sea. The MAGEs distributional patterns varied with environmental conditions. Abstract: The 1- O -monoalkyl glycerol ethers (MAGEs) are traditionally considered as biomarkers for sulfate-reducing bacteria (SRB), but recent studies suggest other biological sources are likely. In this study, we examined the MAGEs in the Yellow River and Bohai Sea. The results show the ubiquitous occurrence of MAGEs in soils, river and marine sediments with the mean concentration one order of magnitude higher in Bohai Sea sediments (91.8 μg/g OC) than in soils (9.8 μg/g OC) and river sediments (12.9 μg/g  OG). The distributional patterns of MAGEs differ between soils and aquatic environments with the maximum at i -C15:0 and n -C16:0, respectively. Comparison of the MAGEs and phospholipid fatty acids reveals that Gram-negative and Gram-positive bacteria and even fungi are all possible biological sources for MAGEs. The abundance ratio of ( n -C16:0  +  m -C17:0 )/( i -C15:0  +  n -C16:0  +  m -C17:0 ) MAGEs gradually increases from soil, river, lake, marginal sea to open ocean, suggesting that the MAGEs can be used for discerning different environmental conditions.